2019
DOI: 10.3389/fphar.2019.00259
|View full text |Cite
|
Sign up to set email alerts
|

Compound Heterozygous CHAT Gene Mutations of a Large Deletion and a Missense Variant in a Chinese Patient With Severe Congenital Myasthenic Syndrome With Episodic Apnea

Abstract: Congenital myasthenic syndromes (CMSs) are a group of inherited disorders caused by genetic defects in neuromuscular junctions. Mutations in CHAT, encoding choline acetyltransferase, cause congenital myasthenic syndrome with episodic apnea (CMS-EA), a rare autosomal recessive disease characterized by respiratory insufficiency with cyanosis and apnea after infections, fever, vomiting, or excitement. To date, no studies have reported deletions comprised of multiple exons. Here, using next generation sequencing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In Table 1 we summarized cases of congenital myasthenic syndrome with neonatal onset previously described and compared them to our case. The literature reported one hundred fifty-five neonatal cases before our case, from 1980 to March 2022 [ 4 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Therefore, of 156 neonates with congenital myasthenic syndrome, nine (5.8%) had vocal cord paralysis, whereas 111 (71.2%) had feeding difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1 we summarized cases of congenital myasthenic syndrome with neonatal onset previously described and compared them to our case. The literature reported one hundred fifty-five neonatal cases before our case, from 1980 to March 2022 [ 4 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Therefore, of 156 neonates with congenital myasthenic syndrome, nine (5.8%) had vocal cord paralysis, whereas 111 (71.2%) had feeding difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, CMS caused by CHAT is classified as a presynaptic form of CMS, and those are estimated to account for only a small percentage of all CMS cases. For example, in Asia, it has been reported in only five families 13,18,49,50 . When the Mayo Clinic conducted a cohort study of CMS patients between 1988 and 2006, only 13 of the 248 identified CMS patients had a CHAT genetic defect 15 .…”
Section: Resultsmentioning
confidence: 99%
“…We sought to evaluate our sifting criteria before proceeding further. To do so, we collected all 36 CHAT SNPs associated with CMS that have been reported so far 9‐14,16‐20,49,50,52‐54 and subjected them to our filtering process. In the first step, 89% (32) mutations were predicted to be deleterious, which is much higher than the 26% we obtained when filtering the 334 unassigned missense mutations.…”
Section: Resultsmentioning
confidence: 99%
“…The most crucial differential diagnosis remains the exclusion of CMS, especially congenital myasthenic syndrome with episodic apnea (CMS-EA), caused by mutations in the CHAT gene, encoding choline acetyltransferase, or the RAPSN gene, encoding a postsynaptic protein, connecting and stabilizing acetylcholine receptors (AChR) at the neuromuscular junction [ 4 ]. Episodes of apnea and respiratory insufficiency are the hallmarks of CHAT pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%